2005
DOI: 10.1002/mnfr.200400042
|View full text |Cite
|
Sign up to set email alerts
|

The residue levels of narasin in eggs of laying hens fed with unmedicated and medicated feed

Abstract: Laying hens were fed contaminated feed containing narasin 2.5 mg/kg for 21 days followed by a 7 day withdrawal period, hens in the control group were fed unmedicated feed. Eggs were collected during trial days 0, 3, 7, 14, 21 and after the withdrawal period of 7 days. The concentration of narasin in yolks and egg whites was analyzed by a liquid chromatography-mass spectrometry method. Narasin was found to accumulate in yolks, where the narasin concentration increased during the treatment. The concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 13 publications
6
29
0
1
Order By: Relevance
“…This has also been demonstrated by other researchers (Rokka et al 2005;EFSA 2007). Feed containing 0.1-5 mg kg À1 lasalocid resulted in whole egg concentrations of 6-8 and 300 mg kg À1 lasalocid, respectively (EFSA 2007).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This has also been demonstrated by other researchers (Rokka et al 2005;EFSA 2007). Feed containing 0.1-5 mg kg À1 lasalocid resulted in whole egg concentrations of 6-8 and 300 mg kg À1 lasalocid, respectively (EFSA 2007).…”
Section: Discussionsupporting
confidence: 78%
“…Rokka et al (2005) found, however, that egg production was not (monensin) or significantly (lasalocid) decreased if laying hens received feed containing monensin at 100 mg kg À1 or lasalocid at 115-150 mg kg À1 , respectively. Orally administered substances need to pass the intestinal wall.…”
Section: Discussionmentioning
confidence: 73%
“…Cross-contamination of feed is a well-known problem and may be due to improperly constructed equipment, poor dust control or inadequate clean-out procedures between sequential batches of feed (FDA 2005). Even very low levels of antibiotic contamination may result in significant residues in food, as confirmed by studies on coccidiostats in poultry feed (Kennedy et al 1998;Rokka et al 2005) and sulfadimidine in swine (Biehl et al 1981;McCaughey et al 1990). Sulfonamides are veterinary drugs routinely used in farm animals and sulfonamide residues in animal products, such as eggs and milk, have recently been investigated (Furusawa and Kishida 2002;Cavaliere et al 2003;Juhel-Gaugain et al 2005).…”
Section: Introductionmentioning
confidence: 79%
“…Eimeria türleri tarafından meydana getirilen, proventrikülden başlayarak kolona kadar olan emilim yollarının harabiyeti ve şiddetli ishalle karakterize olan bu hastalığın tedavi edilmediği takdirde ölümle sonuçlanması kaçınılmazdır. Tedavisinde değişik antibiyotiklerin yanı sıra genelde antikoksidiyal olarak karboksilik iyonoforlar kullanılmaktadır (Parelman, 1993;Rokka, 2005).…”
Section: Introductionunclassified